National REDI Congress 2022 Book of Abstracts - REDi Romblon State University (Romblon State University Research Journal, 2023)
Research Papers under this category are those that bring in new knowledge based on experimental or theoretical work and directed towards a specific aim or objective. They may, however be subjected to further verification. Research outputs that are institutionally or self-funded and have not been published or presented elsewhere are qualified for review. These outputs are further classified as follows: Social Sciences, Humanities and Education (SHE) Papers about economics, history, psychology, sociology, law, literature, language, philosophy, formal and non-formal education. Supervision, Administration, Leadership and Management (SALM) Papers about educational, business and public administration, leadership, management and supervision. Environment, Agriculture and Natural Sciences Papers about agriculture, fishery, forestry, environment, eco-tourism, biology, physical and earth sciences. Engineering, Development and Innovation Papers under this category are scientific outputs that produce new materials, equipment, devices, products, processes, systems and services. They may also include outputs of pilot testing projects, feasibility of technology utilization and gauging end-users’ feedback in the developed and introduced products, devices and systems. Extension Outputs under this category are those that bring the university extension agenda to communities through an informed process of situation analysis, gaps identification and consensus building. This includes community education, technology transfer, advisory work, human resource development and community empowerment in general.